2008
DOI: 10.1080/00365590801950279
|View full text |Cite
|
Sign up to set email alerts
|

Effect of correcting serum cholesterol levels on erectile function in patients with vasculogenic erectile dysfunction

Abstract: Correction of serum cholesterol levels with atorvastatin could improve erectile function in patients who have only hypercholesterolaemia as a risk factor for erectile dysfunction. Furthermore, atorvastatin could improve sildenafil's effects on erectile function in hypercholesterolaemic patients with erectile dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 19 publications
0
32
1
1
Order By: Relevance
“…18,19,21,22,26 Our results do not support this supposed improved response to iPDE5 after the use of simvastatin, although the studies that signal this endothelial modulation used atorvastatin. 16,18,19,22,23,26 It may be that the improved response to iPDE5 reported in these studies is related to the potency of the statin s À1 used. This is suggested by three randomized clinical trials using atorvastatin (from 40 to 80 mg daily), that showed a significant improvement in ED compared with the placebo 19,21,26 after less than 6 months using the medication.…”
Section: Values Expressed In Median (Percentile 25-75) C Values Exprcontrasting
confidence: 56%
See 2 more Smart Citations
“…18,19,21,22,26 Our results do not support this supposed improved response to iPDE5 after the use of simvastatin, although the studies that signal this endothelial modulation used atorvastatin. 16,18,19,22,23,26 It may be that the improved response to iPDE5 reported in these studies is related to the potency of the statin s À1 used. This is suggested by three randomized clinical trials using atorvastatin (from 40 to 80 mg daily), that showed a significant improvement in ED compared with the placebo 19,21,26 after less than 6 months using the medication.…”
Section: Values Expressed In Median (Percentile 25-75) C Values Exprcontrasting
confidence: 56%
“…27 Some authors showed that the treatment of dyslipidemia with The effect of simvastatin in penile erection ET Mastalir et al statins can determine the improvement of ED in selected patients. 16,18,19,[21][22][23]26 The explanations of how statins could improve ED are based mainly on the pleiotropic effects of this class of medication, that is, effects that go beyond simply lowering cholesterol levels. 7,8 Outstanding among these effects are the stabilization and posterior reduction of the atherosclerotic plaque, improved endothelial function and regulation of NO production, with consequent arteriolar vasodilation and diminished inflammatory activity, oxidative stress and thrombotic events.…”
Section: Values Expressed In Median (Percentile 25-75) C Values Exprmentioning
confidence: 99%
See 1 more Smart Citation
“…127,128 There have been several reports of improvements in erectile function among men using statins with and without PDE5 inhibitors. [129][130][131][132] However, these findings are not consistent with those of Solomon et al, 133 who reported new-onset ED in 22% of 93 high-risk men after 6 months of statin use. Placebo-controlled studies of erectile function in men taking medications to control other cardiovascular risk factors are lacking.…”
Section: Mayo Clinic Proceedingsmentioning
confidence: 59%
“…Importantly, the benefits of statin therapy are evident in subjects with mild to moderate CKD but not in those receiving dialysis (as in the 4D trial), strongly supporting early initiation of statin treatment in CKD. 46 There are a number of reports of improved erectile function in men receiving statins with and without phosphodiesterase-5 (PDE5) inhibitors, 48,49 but a recent report showed a high rate of new-onset ED (22 per cent of 93 men after six months of statin use) in subjects with high CV risk, 50 suggesting that late initiation of statin in older patients with comorbidities such as diabetes and multiple CV risk factors may be less effective.…”
Section: Lipid-lowering Therapymentioning
confidence: 99%